Pada KUALITAS DEMOKRASI LOKAL: STUDI KASUS PERUSAKAN KOTAK SUARA PADA PILKADA DI KOTA SUNGAI PENUH TAHUN 2024 - Jazil Baskara; Pratiwi Khairunnisa; Andri Rusta; Irawati; Mhd. Fajri (Jurnal Administrasi Publik dan Pemerintahan, 2026)
This study aims to analyze the quality of local democracy in terms of electoral integrity, public trust, and legitimacy through a case study of ballot box tampering in the 2024 regional elections in Sungai Penuh City. This study uses a qualitative approach by utilizing secondary data obtained from official documents of the Sungai Penuh City KPU and Sungai Penuh City Bawaslu, reports, media coverage, and academic literature on local democracy. The results of this study show that the destruction of ballot boxes was triggered by dissatisfaction with the results of the vote count, as well as strategic political motives to force a re-vote (PSU), organized instructions from certain actors driven by the fanaticism of supporters of the candidates for mayor and deputy mayor of Sungai Penuh. Thus, this study provides an overview that strengthening the quality of local democracy is not only at the stage of improving the integrity of the organizers and the logistics security system, but also requires political education, digital literacy, and strict law enforcement in the implementation of regional elections in Sungai Penuh City.